(untitled) (Research, Society and Development, 2023)
The Igarapé do Mindu is under constant threat of degradation. An alternative that seeks to minimize these damages is bioremediation, a technology that provides significant water quality, in addition to having a low cost. The present work aimed to characterize the physical-chemical and microbiological parameters of a course of the Igarapé do Mindú and to evaluate the use of filamentous fungi for bioremediation of this environment. Samples were collected at 3 points and analyzes were carried out at the Microbiology Laboratory of the Amazon Biotechnology Center (CBA). The physical-chemical parameters were: pH, temperature, electrical conductivity, turbidity, Dissolved Oxygen (DO), Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD) and Nitrogen Compounds (NH4+). Microbiological parameters were total coliforms and Escherichia coli. For the biotreatment, 5 fungi were evaluated. The domestic effluent had a pH in the range of 7, turbidity between 14.05 and 21.45 NTU. Conductivity varied between 429 and 666 µS/cm. The DO was between 0.64 - 1.08 mg/L. The (NH4+) varied between 7.92 and 10.22 mg/L. The values for DBO were between 18.99 and 31.48 and 44.16 and 73.11 for DQO. The analysis of the physical-chemical and microbiological parameters showed a significant degree of environmental degradation, indicating a strong presence of organic matter from waste released into the stream. After 10 days of treatment, the 5 filamentous fungi were able to improve the microbiological parameters of the water in accordance with CONAMA resolution 357/2005.